Proposed Amendments to the Constitution of the International Commission on Zoological Nomenclature - On Zoological Nomenclature, International Commission (Zootaxa, 2020)
The International Commission on Zoological Nomenclature (ICZN, or Commission) considered amendments to Articles of its Constitution (ICZN 1999a) at a special session in Singapore, convened on June 3–7, 2019. During this meeting, Commissioners also planned revisions to the Bylaws, the current International Code of Zoological Nomenclature (ICZN 1999b, 2003, 2012, 2017) and ZooBank user policies.